The effect of socioeconomic factors on malnutrition in Syrian children aged 0-6 years living in Turkey: a cross-sectional study - Vasfiye Bayram Değer; Sema Çifçi; Melikşah Ertem (BMC, 2024)
Abstract Background This study was conducted to examine the prevalence of malnutrition in Syrian immigrant children living in Turkey. Methods The study was carried out in the city of Mardin, which is one of the cities with a high Syrian immigrant population in Turkey. Height, body weight and BMI values were recorded to determine the malnutrition status of the children. Z-scores of children were calculated using the malnutrition assessment WHOAntro program. Results The data show that 30.5% of Syrian children between the ages of 0 and 6 months are male, making up 55.8% of the total, and that 55.3% do not follow a regular breakfast schedule. The percentages of body weight for height, height for age, and BMI for age of Syrian children with a score between − 2 and + 2 SD Number were (89.3%), (74.3%), and (79.3%), respectively. Girls are more likely than boys to experience stunting and low body weight in the context of Syrian children (Stunting OR: 0.855(0.761-1.403), Underweight OR: 0.705(0.609-1,208)). Additionally, there is a link between levels of stunting and underweight and elements like the mother's educational level and the family's income. Contrary to the situation of adequate nutrition, it was discovered that the likelihood of stunting and low body weight in children increased by 0.809 and 1.039 times, respectively, when access to an adequate food supply was not available within the family (p < 0.05). Conclusion s According to the results of the study, gender, family income, mother's education level and access to food affected the severity of malnutrition in children. Migration is an imporatnt factor affecting children's health. In this study malnutrition was found high im immigrant children. Programs should be developed to monitor the growth and development of disadvantaged children and to support their nutrition.